PENERAPAN MODEL PROBLEM SOLVING DENGAN PENDEKATAN KOLABORATIF UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA AKUNTANSI DI SMK NEGERI 1 KISARAN - Julianti, Vina; Thohiri, Roza; Aida Silalahi, Sondang; Gary Ganda Tua Sibarani, Choms; Haryani Sitompul, Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low activity and learning outcomes of students. The purpose of this study is to improve the activity and learning outcomes of 34 students of class X AKL I SMKN 1 Kisaran by applying the problem solving model with a collaborative approach. This study is a classroom action research conducted in two cycles. Data collection techniques in this study are student learning activity observation sheets and learning outcome tests. The data analysis techniques of this study are quantitative data analysis and qualitative data analysis. From the student learning activity observation sheets, in cycle I there were 13 students (38.23%) who were included in the active and very active categories. In cycle II students who were included in the active and very active categories increased to 28 students (82.35%) and had met the success indicator ≥ 75%. The data analysis revealed an average pre-test score of 70.29, with 16 students (47.05%) completing the test. The cycle I post-test averaged 75, with 18 students (52.94%) completing the test. This increased to a cycle II post-test average of 86.47, with 30 students (88.23%) completing the test, meeting the success indicator of ≥85%. Based on this analysis, it can be concluded that the application of a problem-solving model with a collaborative approach can improve the learning activities and outcomes of accounting students at SMKN 1 Kisaran.